Identifikasi Faktor Penentu dan Penolak Adopsi Aplikasi Telemedicine Menggunakan Teori Difusi Inovasi: Diffusion Of Innovation Theory - Gumilang, Wulan Sari; Lazuardi, Garis Rizky; Indrawan, Muhamad Reza; Sulharis, Hafizan Fadli (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The results of research conducted by the Katadata Insight Center regarding the use of health and telemedicine services in Indonesia from 28 February – 7 March 2022 found that 8% of respondents chose telemedicine services, while 33% chose to seek treatment/consultation from a doctor directly, 27% chose to look for related information symptoms of disease felt via the internet, 19% chose to buy medicine directly, 11% chose to drink herbal medicine/concoction, and the remaining 2% chose to let the disease heal itself [10]. The survey was conducted online with an age criterion of 16 years. The total number of respondents who took part in this online survey was 2,108 people spread across 34 provinces. From the results of this research, it can be concluded that the use of telemedicine as an alternative to online health consultation services is still relatively small. In this research, the approach used is a qualitative approach (qualitative research). The qualitative method is a non-numerical research technique where people are involved as research instruments. The results of this research show that relative advantage, compatibility, and trialability are factors in the adoption of telemedicine applications at Paramadina University. Of these three characteristics, relative advantage is the most dominant characteristic in this research from the user's perspective. Informants feel that there are advantages in using telemedicine applications, such as helping to get faster and more efficient services, telemedicine applications can also be relied on when needed, such as when there is no time to visit a doctor at a hospital or clinic, using telemedicine applications is also easy to do and learn so it is easy. to understand.